Laboratory Identification of Lupus Anticoagulants: Results of the Second International Workshop for Identification of Lupus Anticoagulants - Brandt, John T; Barna, Linda K; Triplett, Douglas A (Thrombosis and Haemostasis, 1995)
Lupus anticoagulants (LAs) are antibodies that interfere with phospholipid dependent coagulation reactions in vitro. This workshop was designed to provide the participants with an experience in identification of LAs, to evaluate different criteria for mixing studies, to assess the performance of recently introduced confirmatory studies and to assess the performance of two potential surrogate LA control plasmas. The results demonstrate that there continues to be significant variation in the sensitivity and responsiveness of APTT reagents to the presence of LAs, confirming the need for more than one screening assay before the presence of a LA can be ruled out. In this workshop, the best distinction between factor deficiency and inhibitors was obtained using a 1:1 mix of normal plasma with patient plasma and the criterion defining correction as shortening of the APTT to within 5 s of the APTT of pooled normal plasma. A 4:1 mix of patient to normal plasma did not work well in distinguishing factor deficiency from inhibitors. The platelet neutralization procedure, DVVconfirm® and StaClot LA® all gave positive results with the LA samples. False positive platelet neutralization procedures were seen with the samples from patients on oral anticoagulants and a factor V inhibitor. False positive StaClot LA results were obtained with high titer factor VIII inhibitors. Both of the potential surrogate plasmas gave variable results with multiple assays; they can not be recommended for routine use at present.